Mekanisme Islamic Corporate Governance Pada Kinerja Bank Umum Syariah Menggunakan Islamic Performance Index - Puspasari, Oktaviani Rita (Program Studi Akuntansi, Universitas Kuningan, 2017)
This study examine how Islamic Corporate Governance mechanism which are : a number of sharia supervisory board meeting, independent directors, a number of audit committee meeting has an effect to the Islamic Bank performance in Indonesia which meassured by Islamic Performance Index, which proxy by : Profit sharing ratio (PSR), Islamic Income Ratio (IIR) and Equitable Distribution Ratio (EDR). The sample selection method is purposive sampling and obtained 9 Islamic bank in 5 years period observation with 45 data are being sampled. Multiple regression analysis is used to analyze the data. The results shows that a number of DPS meeting have a negative effect to PSREDR, however positive effect showed for IIR. Then, independent directors have a negative effect to the PSR and IIR, however it has positive effect for EDR. As well as, negative effect showed by a number of audit committee meeting to PSR and IIR, while a number of audit committee meeting have positive effect for EDR. However the analysis result show that there are no significant effect from independent variable to the Islamic Bank performance which measured by Islamic Performance Index.Keyword: A number of Sharia Supervisory Board meetings, Independent Directors, a number of audit committee meeting, Islamic Bank Performance.